Development of STEM-based Teaching Modules Integrated with the Pancasila Student Profiles for Primary School - Barumbun, Mardyanto; Oktaviah, Fina Nur; Dwiyanti, Anik; Suyadi, Suyadi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This study aims to develop STEM-based teaching modules for primary 4 students that are integrated with the Pancasila Student Profile. This research was conducted according to developmental research (R&D) procedures. The modules were developed based on the needs of teachers and students obtained through observation, interviews, and a diagnostic test to students. The validation from experts on the modules showed very good categories for each material, layout and graphics aspect. Moreover, the modules developed are considered very practical to teachers in class, while students’ responses for the learning using the modules are very positive. Hence, the students' learning achievements are very satisfactory.